Market efficiency in developed and emerging markets. (2015) - Sharma, Ankit; Thaker, Keyur
The weekly and monthly returns of stock indices and portfolios of stock indices were analysed to investigate the weak form of market efficiency in developed and emerging capital markets using standard tests of market efficiency. Our results, based on an analysis of 13 years of data, show mixed results for different indices. However, portfolio returns of developed and emerging markets indicate the absence of market efficiency. Developed markets show inefficiency for monthly returns that is contrary to the conventional perception that developed markets are efficient in comparison to emerging markets owing to their long existence, better maturity, depth and technological development.